Incidence and Prevalence of Alzheimer’s Disease in Medicare Beneficiaries - Haixin Zhang; Amir Abbas Tahami Monfared; Quanwu Zhang; Lawrence S. Honig (Neurology and Therapy)
Abstract Introduction The availability of anti-amyloid therapy for mild cognitive impairment (MCI) due to Alzheimer’s disease and mild Alzheimer’s dementia (AD) has underscored the need for realistic estimates of the population with AD/MCI within the healthcare system to assure adequate preparedness. We hypothesize that administrative databases can provide real-world epidemiologic estimates reflecting the population with diagnosed (known) MCI and AD. This study was conducted to estimate diagnostic incidence and prevalence of AD and all-cause MCI among the Medicare fee-for-service (FFS) and Medicare Advantage (MA) beneficiaries in the United States. Methods This was a retrospective analysis of Medicare beneficiaries (aged 65 and older) with identified diagnoses of AD/MCI based on ≥ 2 diagnostic codes ≥ 30 days apart. Incidence/prevalence estimates were reported per 10,000 person-years. Results In FFS, AD incidence (2008–2018) decreased (138 to 104); MCI incidence increased (8 to 47), but the sum (MCI + AD) was relatively stable (146 to 151). Prevalence (2008–2017) increased for AD (318 to 354), and MCI (13 to 99). In MA (2016) epidemiological estimates were consistent with FFS. In 2017, older age, female sex and the Northeastern region were consistently associated with higher AD/MCI prevalence among FFS beneficiaries. Conclusion In FFS, AD/MCI diagnostic prevalence increased over 10 years, especially for MCI; prevalence estimates in MA (2016) were comparable. Diagnostic prevalence in 2016 (FFS + MA) was 3.4% for AD and 0.85% for MCI. Our findings address the reality of Alzheimer’s disease in clinical practice in the United States that is confronted by healthcare professionals, payors, healthcare decision-makers, patients, and caregivers, and may offer a realistic gauge for patient triage for treatment, healthcare resource allocation, and health-systems’ operational prioritization. With the availability of anti-amyloid treatments, we anticipate that the population with diagnosed MCI/AD within the Medicare database may rise over time; therefore, periodic updates of incidence/prevalence estimates may provide support for timely healthcare decision-making.